Total Factor Productivity Change and Reforms of Managed Inpatient Flow at Landspitali University Hospital - Guðmundur I. Bergþórsson 1968- (2011)
The aim of this dissertation is to measure changes in Total Factor Productivity (TFP) and examine possible causes of such changes following reforms of managed inpatient flow at Landspítali - University Hospital (LUH) in Iceland. The change in TFP is measured as the difference in TFP that occurs within two periods of time, specifically January to March 2007 and January to March 2009. The motivation behind this study is to measure the changes in TFP, as it is a meaningful yardstick by which to measure economic changes surrounding hospital activity. The research method used is a combination of Data Envelopment Analysis and the Malmquist Index methods (DEA-MI). These methods are used for comparing the TFP of five selected wards between two different periods, i.e., the period of January to March 2007 and the period of January to March 2009. From an economical perspective, after the implementation of the reforms, the findings reveal that there is an average of approximately 3% decreased TFP in inpatient flow at LUH’s wards under examination between the periods of January - March 2007 and January - March 2009. The cause of TFP changes measured by the variables used, Working-Load-Index and Lay Days, is not completely distinguishable, i.e., whether the cause of the decreasing TFP is caused by changes in scale efficiency or technical changes. The main conclusion drawn from this work is that TFP decreased slightly or at least was unchanged following the inpatient-managed reform when calculating the change in TFP through the DEA-MI method. The main recommendation, from both theoretical and practical viewpoints, is to take advantage of the reliability of the DEA-MI method to measure the TFP change between wards, specializing in various medical areas, within the same hospital. In addition, Hospital managers can benefit from utilizing and elaborating on appropriate and improved methods to measure their success.